2008
DOI: 10.1016/j.bmcl.2007.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of mechanism-based inhibitors for the tyrosine aminomutase SgTAM

Abstract: The synthesis and evaluation of two classes of inhibitors for SgTAM, a 4-methylideneimidazole-5-one (MIO) containing tyrosine aminomutase, are described. A mechanism-based strategy was used to design analogs that mimic the substrate or product of the reaction and form covalent interactions with the enzyme through the MIO prosthetic group. The analogs were characterized by measuring inhibition constants and X-ray crystallographic structural analysis of the co-complexes bound to the aminomutase, SgTAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Such a structure could be essential for flexibility and plasticity of the enzyme and seems to be a functional requirement for substrate binding and catalysis. Data indicated that TbPAM has the same overall protein fold as tyrosine aminomutase (Sg-TAM) that was reported by Montavon and coworkers (11). Moreover, superposition of the theoretical structure of TbPAM with TAM and PAL indicated significant homology where TbPAM contains a 4-methylidene-imidazole-5-one (MIO) cofactor.…”
Section: Predicted Structure and Active Site Of Tbpamsupporting
confidence: 63%
“…Such a structure could be essential for flexibility and plasticity of the enzyme and seems to be a functional requirement for substrate binding and catalysis. Data indicated that TbPAM has the same overall protein fold as tyrosine aminomutase (Sg-TAM) that was reported by Montavon and coworkers (11). Moreover, superposition of the theoretical structure of TbPAM with TAM and PAL indicated significant homology where TbPAM contains a 4-methylidene-imidazole-5-one (MIO) cofactor.…”
Section: Predicted Structure and Active Site Of Tbpamsupporting
confidence: 63%
“…Strong evidence for this latter mechanism comes from X-ray crystallographic work on TAM that had been inactivated by tyrosine analogues in which the a-hydrogens are substituted with fluorine atoms. [20,27] The use of these compounds, which cannot undergo ammonia elimination resulted in the formation of covalent adducts between MIO and the amino group of the analogues. This suggests that MIO might be coupled with the amino group of the substrate in the initial stage of the aminomutase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent biochemical characterizations of SgcC4 have established that it (i) specifically catalyzes the conversion of L-tyrosine to (S)-β-tyrosine, shunting the primary metabolite into the C-1027 biosynthetic pathway, and (ii) releases 4-hydroxycinnamic acid as an intermediate, spuriously revealing weak activity as an ammonia lyase (7,8). Crystal structures have been solved for SgcC4 either alone or with mechanism-based inhibitors, as well as for the active site mutant SgcC4 (Tyr70Phe) with bound L-tyrosine (9)(10)(11)(12). These structures (i) unambiguously demonstrate the presence of the MIO prosthetic group, (ii) define the active site residues responsible for catalysis and substrate binding, and (iii) in comparison with structures of MIO-containing ammonia lyases, provide a method to bioinformatically differentiate MIO-containing aminomutases from ammonia lyases (3)(4)(5).…”
Section: Streptomyces Globisporusmentioning
confidence: 99%
“…Mechanistic and structural characterizations of the MIO-containing aminomutases as a family have unveiled much unique chemistry, enzymology, and structural biology (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and exploitation of these enzymes as biocatalysts has provided access to α-and β-amino acids, which are difficult to prepare by other means (4,37). However, ʟ-phenylalanine and ʟ-tyrosine remain the only two known natural substrates (3)(4)(5).…”
Section: ·Smentioning
confidence: 99%
See 1 more Smart Citation